Chemistry Learning Through Practicum With Household Materials During The Covid-19 Pandemic - Sunyono, Sunyono; Sugiarti, Rini (FKIP Universitas Lampung, 2021)
Learning Chemistry Through Practicum With Household Materials During the Covid-19 Pandemic. Purpose: This study aims to improve students’ learning interest and understanding the chemical concepts after participating in chemistry learning through practicum using household chemical materials during the Covid-19 pandemic. Method: This research was conducted through the classroom action research with three cycles of action. The research was conducted on Grade X SMKN 1 Natar Lampung Selatan with 32 students. Finding: After learning, it was found that (1) there is an increase of student interest in the category of “very high” 79.84% and “high” amounting to 12.03%, other categories are the low category of 7.19% and 0.94% very low category. (2) Students’ understanding of chemistry concepts increased from cycle to cycle with an increase in cycle 1 to cycle 2 of 2.00 points and from cycle 2 to cycle 3 of 8.50 points. Conclusion: The online chemistry study during the Covid-19 pandemic through practicum using household chemical materials can increase students’ learning interest and understanding of chemistry concepts.Keywords: chemistry practicum, household chemical materials; Covid-19 pandemic. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202111